Strategy and Function of Perfect Health's Public Relations Activities in Enhancing a Positive Image through Philanthropic Corporate Social Responsibility - Geofakta Razali; Rizki Hidayat (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Efforts to reduce poverty rate are still a highlighted issue almost in every country. Especially during the COVID-19 pandemic, there is increasing attention to corporate social responsibility (CSR) around the world, to find out the magnitude of its influence on corporate image as can be seen from its Â sustainable, accountable and transparent implementation. Perfect Health carries out several strategies to realize Â the function of Public Relations activities through CSR Philanthropy in the program "compensation for orphans, disaster donations, social actionâ€, with the aim of Â influencing Â other people through cognitive, affective and conative aspects. The researchers use a qualitative research method approach to collect data from some relevant sources for analysis through public relations theoretical approach. Informants in this study comprise community members, philanthropic institutions, and perfect health public relations officers. Data are collected through observation, interviews, questionnaires and literature study techniques. The results show that the implementation of CSR has a positive impact on company image. Furthermore, this study proposes that CSR philanthropy helps promote positive attitudes which in turn increase peopleâ€™s behavioral interests.